DIPG-15. PNOC-003: CLINICAL IMPACT OF A PRECISION MEDICINE STRATEGY FOR CHILDREN WITH DIFFUSE INTRINSIC PONTINE GLIOMA. (23rd April 2019) - Mueller, Sabine; Kline, Cassie; Kilburn, Lindsay; Liang, Winnie S; Jain, Payal; Gupta, Nalin; Panditharatna, Eshini; Nazemi, Kellie; Magge, Suresh N; Crawford, John; Banerjee, Anu; Packer, Roger; et al.
Abstract: OBJECTIVE: We evaluated the impact on overall survival at 12 months (OS12) of a personalized therapy plan based on tumor/germline whole exome (WES) and tumor RNA sequencing (RNAseq) of diffuse intrinsic pontine glioma (DIPG). METHODS: We enrolled newly diagnosed DIPG patients ≤ 25 years of age. Tumors were sequenced and drug selection was performed using a custom drug-matching pipeline and pharmacopeia. A personalized treatment strategy using up to 4 FDA-approved drugs was determined by a specialized tumor board with target of 21 business days from biopsy. Patients were followed for adverse events (AEs) and OS12. Circulating tumor DNA (ctDNA) was collected at diagnosis and with surveillance MRIs. Xenograft development and cell culture expansion were attempted for each patient. RESULTS: Nineteen patients (6 females; median age 6 years; range 4–25 years) followed therapy recommendations. Average mapped coverages for WES were 490X (tumor) and 194X (germline). An average of 245, 951, 030 total mapped reads was achieved for tumor RNA. Panobinostat was the most commonly recommended drug (n=12; 63%). The multi-agent therapy plan was well tolerated with mainly grade 1/2 AEs. Grade 3/4 AEs were predominantly hematologic, including thrombocytopenia (n=13; 22%) and neutropenia (n=16; 27%). The OS12 did not significantly differ from historical controls (OS12 0.47; 95% CI 0.24, 0.70) or from a feasibility cohort that did not follow tumor board recommendations (OS12 0.66; 95% CI 0.36, 0.97; p=0.34). Fourteen DIPG cell lines were established. CtDNA analysis at diagnosis confirmed the H3K27M mutation in 16/20 patients, known to harbor H3K27M in tumor. CONCLUSION: A multi-agent therapy recommendation based on WES and RNAseq analysis of DIPG tumors is feasible; however, there is no demonstrated impact on clinical outcome. This is likely due to lack of efficacious FDA-approved drugs that target key mutations in DIPG, as well as molecular evolution of these tumors.